Democracy, cities and space: South African conceptions of local government - Chipkin, Ivor (My University, 1997)
In 1988 the Soweto People's Delegation and the councils of Soweto, Diepmeadow and Dobsonville began to negotiate an end to the rent boycott and the crisis in the provision of services. Discussions between civic bodies and local government officials - which eventually resulted in the Soweto accord - were increasingly infonned by the slogan 'one city, one tax base'. In the wake of the accord, other parties to similarly established negotiations commonly based their approach on the 'one city' slogan. As a result, local government negotiations and the institutional arrangements that followed were increasingly infonned by this notion. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted in the Faculty of Arts, University of the Witwatersrand, in the fulfillment of the requirements for the degree Master of Arts in Political Studies. Johannesburg 1997.
Keywords: Local government--South Africa--Gauteng.; South Africa--Politics and government--1989-1994.; Witwatersrand ( South Africa )